Current state and future prospects of immunotherapy for glioma. (9th February 2018) - Kamran, Neha; Alghamri, Mahmoud S; Nunez, Felipe J; Shah, Diana; Asad, Antonela S; Candolfi, Marianela; Altshuler, David; Lowenstein, Pedro R; Castro, Maria G
There is a large unmet need for effective therapeutic approaches for glioma, the most malignant brain tumor. Clinical and preclinical studies have enormously expanded our knowledge about the molecular aspects of this deadly disease and its interaction with the host immune system. In this review we highlight the wide array of immunotherapeutic interventions that are currently being tested in glioma patients. Given the molecular heterogeneity, tumor immunoediting and the profound immunosuppression that characterize glioma, it has become clear that combinatorial approaches targeting multiple pathways tailored to the genetic signature of the tumor will be required in order to achieve optimal therapeutic efficacy.